Synthesis and Characterization of Some 1,4-Dihydropyridine Derivatives Containing Dichlorothiazolyl Substituents - TAGHI-GANJI, K.M.; GHODSI, SH.; ALIPOUR, E.; AMINI, M.; HOSSEINI, M.; SHAFIEE, A. (Asian Journal of Chemistry, 2010)
4-Substituted heterocycles or aryl dihydropyridines (DHP) with various C3, C5 diesters have calcium channel antagonist activity. In this paper a group of dialkyl, dicycloalkyl and diaryl ester analogues of nifedipine, in which the ortho nitro phenyl group at position 4 is replaced by 2,4-dichloro-5-thiazolyl substituent is presented. The Hantzsch condensation of alkyl acetoacetate (3) and ammonium acetate with 2,4-dichloro-1,3-thiazole-5-carboxaldehyde (2) offered symmetrical dialkyl 1,4-dihydro-2,6-dimethyl-4-(2,4-dichloro-1,3-thiazolyl)-3,5-pyridinedicarboxylates. Whereas condensation of 2 with 3 and 5 gave the asymmetrical dialkyl esters.